Effect of primary aldosteronism on diabetes mellitus and hypertension: a short narrative review - Ghimire, Rajan (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Primary aldosteronism (PA) is a condition of excess aldosterone levels due to a pathology of the adrenal gland. Diabetes and hypertension increase cardiovascular, renal, and cerebrovascular morbidity and mortality. If diabetes and hypertension coexist with underlying PA, complications increase. PA is usually not screened in every individual due to the cost and technical difficulties associated with the test. There are certain guidelines to screen for PA, like resistant hypertension with more than three antihypertensive agents, family history of PA, young-onset hypertension, diuretic-induced hypokalemia, etc. PA increases insulin resistance. It is still debatable whether PA poses a risk for new-onset diabetes mellitus or not. However, there is a consensus that PA increases metabolic and vascular complications in diabetic and hypertensive patients. The main aim of this article is to highlight a few aspects of aldosteronism and its impact on diabetes and hypertension.Method: It is a short narrative review article. Articles were searched over PubMed and Google Scholar using the search words Primary Aldosteronism “And “Or” Diabetes mellitus. Full articles were only reviewed.Result: PA is one of the common causes of secondary hypertension. It is not screened in all patients. Reviewed research papers support screening for PA in patients with resistant hypertension with more than three antihypertensive agents, family history of PA, young-onset hypertension, and diuretic-induced hypokalemia.Conclusion: It is better to screen and treat PA in diabetic and hypertensive patients as per the screening guidelines released by the relevant Societies of Endocrinologists and the location of health institutes.